TO THE QUESTION OF VIBRO-EXCITER’S ENERGY EFFICIENCY INCREASING FOR VIBRATING COMPACTORS IN THE SPHERE OF ROAD CONCTRUCTION - M. K. Shushubaeva; V. V. Miheev; S. V. Savelev (Вестник СибАДИ, 2018)
Introduction. The article considers the relevance of the subject of using vibratory compactors in the road construction field. Moreover, the shortcomings of existing unbalance exciters are revealed. In order to eliminate the drawbacks, we propose a new design of a crank-rod type vibration exciter. Therefore, the design is a new step in the development of directional oscillators, the use of which in road engineering would increase its productivity and efficiency. The main provisions, which allow to calculate energy efficiency and vibration parameters of a new exciter, are considered. The results of calculations and the dependence of the power exponent for the entire period of oscillatory motion are presented. The article proposes a new principle of designing periodic generators of directed force action. The scheme of the construction and its kinematic scheme are presented. The result of the research is to increase the energy efficiency of using vibrating compactors in road construction. Material and methods. A new design of a vibration exciter is presented, the dependence character of the direction of the driving force on time relative to the treated surface is revealed. Results. Increase energy efficiency of the building materials’ processing by vibrating road rollers are given. Discussion and conclusion. As can be seen, the proposed technical solution is a new step in the development of oscillators of directional action and their usage in road engineering, which would improve its productivity and efficiency of processing road building materials.